Reading the Fossils of Faith: Thomas Henry Huxley and the Evolutionary Subtext of the Synoptic Problem - Day, Matthew (Church history, 2005)
In a book loaded with metaphors of assault and retaliation, Andrew Dickson White's A History of the Warfare of Science with Theology in Christendom saved one of the best for Darwin. “Darwin's Origin of Species,” we are told, came “into the theological world like a plough into an ant-hill. Everywhere those thus rudely awakened from their old comfort and repose had swarmed forth angry and confused.” For White, the sometimes frenzied post-Darwinian controversies over providential design and divine creation were simply the latest episodes in an all-out struggle between theology and science that stretched back beyond Galileo's cheerless encounters with the Catholic Church. Though the voices may have been different, the song remained the same. Despite its continuing presence in the popular media, contemporary historians of religion and science now regard White's warfare thesis as an artifact of the constantly shifting relationships between these two cultural fields rather than a viable analysis of their engagement. The fundamental problem with the conflict model is that it is a bit like performing heart surgery with a Phillips head screwdriver: it is simply too blunt of an instrument for getting at the all-too-crucial particulars. As a result, it is likely to do more harm than good. To see why, consider what James Moore has called the “religious filiation” of Charles Darwin's evolutionary thought.